Radiochemotherapy with paclitaxel: synchronization effects and the role of p53 - Wenz, Frederik; Greiner, Stefan; Germa, Florence; Mayer, Karin; Latz, Detlev; Weber, Klaus-Josef (Strahlentherapie und Onkologie, 1999)
PURPOSE: We have studied the interaction of paclitaxel (Taxol) and radiation in V79 cells and human lymphoblasts with special emphasis on cell cycle effects and the role of p53. - MATERIAL AND METHODS: V79 cells in log- and plateau-phase and human lymphoblasts (p53wt TK6 and p53mut WTK1) were used. Paclitaxel was given for 2 hours. Survival was determined using clonogenic assays. Cell cycle analysis was done using DNA flow cytometry. - RESULTS: In V79 cells there was a dose dependent delay of colony formation after paclitaxel. The LD50 was about 0.4 microM with a 2-hour exposure. In exponentially growing cells, there was an accumulation of 40% of cells in G2/M 6 hours after paclitaxel. The dose modification factor was about 3.9 when radiation was given 6 hours after 0.3 microM paclitaxel for 2 hours. Synchronization experiments using serum starvation and induction showed that synchronization was not sufficient to induce a comparable dose modification factor. Human lymphoblasts with mutated p53 (WTK1, LD50 = 75 microM) were more resistant to paclitaxel than wild type p53 cells (TK6, LD50 = 25 microM). - CONCLUSION: The radiosensitization induced by paclitaxel was critically dependent on the timing of irradiation and chemotherapy, although synchronization alone was not sufficient to explain the dose modification. Lymphoblasts with mutated p53 were less sensitive than wild type p53 cells.